2002
DOI: 10.1046/j.1475-1313.2002.00017.x
|View full text |Cite
|
Sign up to set email alerts
|

Optometric function in visually sensitive migraine before and after treatment with tinted spectacles

Abstract: Optometrists frequently encounter patients with migraine and patients and practitioners sometimes suspect that visual stimuli or visual anomalies trigger headaches. There is a lack of evidence-based research on the issue, however. Some patients with migraine may be hypersensitive to visual stimuli, and it has been suggested that individually prescribed coloured filters might be an effective treatment to reduce symptoms from such stimuli. A recent randomised controlled trial showed such a treatment to be effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
66
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 40 publications
3
66
0
2
Order By: Relevance
“…This review did not relate specifically to migraine, so will not be described in detail. Evans et al (2002), in a study described in the next section, found no significant difference between a group of migraine and a group of control patients in the subjective refractive error or in the proportion of participants who wore spectacles.…”
Section: Refractive Errors and Migrainementioning
confidence: 88%
See 4 more Smart Citations
“…This review did not relate specifically to migraine, so will not be described in detail. Evans et al (2002), in a study described in the next section, found no significant difference between a group of migraine and a group of control patients in the subjective refractive error or in the proportion of participants who wore spectacles.…”
Section: Refractive Errors and Migrainementioning
confidence: 88%
“…They therefore did not represent a ÔnormalÕ group of migraine sufferers. Evans et al (2002) did find using one test method, that the migraine group tended to have a marginally decompensated exophoria at near; however, other test methods suggested that the migraine group were as able to compensate for their exophoria as the control group.…”
Section: Refractive Errors and Migrainementioning
confidence: 92%
See 3 more Smart Citations